Retention prediction of monoamine neurotransmitters in gradient liquid chromatography - Urban, Jiří; Nechvátalová, Martina; Hekerle, Lukáš (Journal of separation science, 2022)
Retention prediction of monoamine neurotransmitters has been compared for the generally applied linear solvent-strength model and quadratic polynomial three-parameter model. The design of experiments protocol has been applied to plan linear gradients within the experimental space with altered gradient time, mobile phase flow rate, and column temperature. Relative prediction errors increased at elevated temperature, which is more significant for the linear solvent-strength model when compared to the polynomial model. On the other hand, the predefined design of experiments space controls the retention time errors, as predictions for LC conditions that are outside of the plan are much less accurate and should be avoided. The final part of the work deals with the effect of extracolumn band dispersion on the peak capacity of linear gradients at various gradient times, mobile phase flow rates, and column temperature. The peak capacity determined for corrected experimental data were consistent with the published results dealing with the optimization of peak capacity in gradient elution.
Keywords: extracolumn volume; indikátory a reagencie; rozpouštědla; neurotransmiterové látky; peak capacity; retention modeling; Solvents; Chromatography, Liquid; Indicators and Reagents; Neurotransmitter Agents; gradient elution; chromatografie kapalinová; Linear Models; lineární modely; design of experiments